Functional delivery of viral miRNAs via exosomes - Pegtel, D Michiel; Cosmopoulos, Katherine; Thorley-Lawson, David A; van Eijndhoven, Monique A J; Hopmans, Erik S; Lindenberg, Jelle L; de Gruijl, Tanja D; Würdinger, Thomas; Middeldorp, Jaap M (Proceedings of the National Academy of Sciences - PNAS, 2010)
Noncoding regulatory microRNAs (miRNAs) of cellular and viral origin control gene expression by repressing the translation of mRNAs into protein. Interestingly, miRNAs are secreted actively through small vesicles called "exosomes" that protect them from degradation by RNases, suggesting that these miRNAs may function outside the cell in which they were produced. Here we demonstrate that miRNAs secreted by EBV-infected cells are transferred to and act in uninfected recipient cells. Using a quantitative RT-PCR approach, we demonstrate that mature EBV-encoded miRNAs are secreted by EBV-infected B cells through exosomes. These EBV-miRNAs are functional because internalization of exosomes by MoDC results in a dose-dependent, miRNA-mediated repression of confirmed EBV target genes, including CXCL11/ITAC, an immunoregulatory gene down-regulated in primary EBV-associated lymphomas. We demonstrate that throughout coculture of EBV-infected B cells EBV-miRNAs accumulate in noninfected neighboring MoDC and show that this accumulation is mediated by transfer of exosomes. Thus, the exogenous EBV-miRNAs transferred through exosomes are delivered to subcellular sites of gene repression in recipient cells. Finally, we show in peripheral blood mononuclear cells from patients with increased EBV load that, although EBV DNA is restricted to the circulating B-cell population, EBV BART miRNAs are present in both B-cell and non-B-cell fractions, suggestive of miRNA transfer. Taken together our findings are consistent with miRNA-mediated gene silencing as a potential mechanism of intercellular communication between cells of the immune system that may be exploited by the persistent human gamma-herpesvirus EBV.